Hemotropic Mycoplasma ovis infection in goats with concurrent gastrointestinal parasitism in Malaysia (Journal of Advanced Veterinary and Animal Research, 2015)
Hemotropic  Mycoplasmosis  is common in sheep  and goats  worldwide,  which  leads  to  huge  economic losses.  In  this  study,  ten  goats  each  were  sampled from  five  herds  belonging  to  the  Ladang  Angkat, Faculty  of  Veterinary  Medicine  (FVM)  for  the assessment  of  Mycoplasma  ovis  infection  and concomitant  intestinal  parasites  burden.  Giemsa stain  and  Modified  McMaster  techniques were used to  study  the  hemotropic  mycoplasmosis  and gastrointestinal  parasite  burden,  respectively. Questionnaires  were  equally  administered  to  each farmer and a fly  trap  was  used  to  trap  biting  flies around the goat herds.  Out of  50  samples analyzed, 94.0%  ( n = 47/50)  were  positive  for  M.  ovis infection.  Among  the  positive  samples,  93.6% (n=44/47)  were  mild  infection  while  6.4%  (n=3/47) were  moderate  infection, with  highest  infection  rate of  38.5%  parasitemia.  There  was  a  significant association  (P